Pengaruh Modernisasi Sistem Administrasi Perpajakan Terhadap Intensi Kepatuhan Pajak (Studi Kasus Mahasiswa Universitas Islam Malang) - Maulana, Moh Irham; Sudaryanti, Dwiyani; Mahsuni, Abdul Wahid (e_Jurnal Ilmiah Riset Akuntansi, 2024)
Charges have a really imperative part for state incomes that are utilized to fund government investing and national improvement. The government looks for to progress the charge organization framework by building up a present day assess organization framework so that charge collection is more idealize and can optimize charges as a source of state income. Modernization of the assess organization framework is carried out to move forward the ability of the Directorate Common of Charges to oversee the usage of assess approaches in understanding with the standards of great administration. With the usage of a present day assess organization framework, backed by quality Human Assets, it is anticipated to create good administration standards based on straightforwardness, responsibility, responsiveness, autonomy and decency.Keywords : Taxation, tax administration system, modernization, good governance,  revenue optimization,